Teacher training and internships. Proposed guidelines for schools - Gianluca Consoli; Giordana Szpunar; Patrizia Sposetti; Pietro Lucisano (Firenze University Press, 2019)
This paper presents the results of a study on the first year of direct internships as a part of the Sapienza University of Rome's Primary Education Sciences degree course (LM 85-bis) in the academic year 2017-2018. Out of this study came a theoretical-operational contribution which focuses on the perception the interns had of the schools hosting them. This work led to the development of proposed guidelines for schools selected for LM 85-bis degree course internships.   La formazione al lavoro dei futuri insegnanti attraverso il tirocinio. Una proposta di linee guida per le scuole L'articolo riporta i risultati di un'indagine sul primo anno di tirocinio diretto nel corso di laurea magistrale (LM 85-bis) in Scienze della formazione primaria dell'Università di dell'Università di Roma "Sapienza" nell'anno accademico 2017-2018. A partire da tale esperienza è stato elaborato un contributo teorico-operativo focalizzato sulla percezione che i tirocinanti hanno delle scuole ospitanti. Il lavoro ha permesso di elaborare una proposta di linee guida per le scuole che ospitano i tirocinanti dei corsi di laurea magistrale 85-bis.